A Retrospective study on the use of oral hypoglycemic agents in elderly patient with diabetes mellitus type 2 - Cai, Jeff Benedict V.; Utanes, Rene Mar E.
Geriatric patients reduced renal and hepatic function predisposes them to adverse effects related to drug therapy. This could be extremely fatal in geriatric patients who were receiving oral hypoglycemic agents (OHA's) due to the possibility of developing hypoglycemic coma. This study evaluated the drug utilization pattern of OHA's in a private tertiary hospital in Laguna for geriatric patients with diabetes mellitus type 2. A retrospective descriptive study was conducted by review of medical records of in-patient aged 60 years or older who were diagnose with diabetes millitus type 2, receive at least one OHA during their hospital stay and were admitted between 01 February 2012 and 31 January 2013. Patient who had undergone solely insulin therapy were excluded from the study. Medical records of 44 patients were received for compliance with international standard clinical practice guidelines, and for drug therapy problems which include contraindication, drug-drug interaction, presence of an adverse drug event, and over utilization. Result indicate that the most commonly used OHA is metformin while the most common patient of therapy is dual OHA therapy, specifically the biguanide sulfonylurea combination. On the other hand, the most commonly occurring drug therapy problem is administration of OHA among contraindicated patients (50%), follow by drug-drug interactions (40.91%), adverse drug events (6.82%), overutilization (2.27%). Result indicate non-compliance with guidelines and recommendations of the American Diabetic Society, American Association of Clinical Endocrinologist and American Geriatric Society, This results may be utilized in initiating adjustments and modifying therapy in management of diabetes mellitus type 2 in geriatric patients at both physician and institutional levels.
Thesis (BS Pharmacy)--University of the Philippines Manila, 2013
Keywords: Drug utilization; Hypoglycemic agents